River-derived sediment suspension and transport in the Bohai, Yellow, and East China Seas: A preliminary modeling study. (1st December 2015) - Zeng, Xiangming; He, Ruoying; Xue, Zuo; Wang, Houjie; Wang, Yue; Yao, Zhigang; Guan, Weibing; Warrillow, Jennifer
Abstract: Coastal circulation and transport of sediment derived from the Huanghe and Changjiang Rivers in the Bohai, Yellow, and East China Seas (BYECS) over the past 48 years (1958–2005) were simulated and analyzed using the Coupled Ocean–Atmosphere–Wave–Sediment Transport modeling system. Model skill assessments against in situ wave and hydrographical observations indicate the model simulation can reasonably well reproduce the hydrodynamic environment of the BYECS. Model-simulated regions of high fine sediment accumulation rate correlate well with the observed regions, which are known as "muddy patches." Bottom stress analysis further indicates that the formation of muddy patches near river mouths is largely due to their proximity to the sediment source. Muddy patches formed in regions farther away from river mouths are results of local weak bottom stress and associated circulation pattern. Simulated seabed sediment distribution reveals that most of the Huanghe-derived sediment stays inside the Bohai Sea, whereas the Changjiang-derived sediment can spread into both the Yellow and East China Seas. Strong seasonal variations exist in the river-derived sediment transport with stronger (weaker) offshore sediment transport occurring in the winter (summer). Highlights: Huanghe and Changjiang-derived sediment transport is simulated over the past 48 years (1958–2005). Model can generally reproduce observed hydrodynamic environment and sediment transport pattern. The formation of muddy patches near river mouths is largely due to their proximity to the sediment source. Muddy patches formed in regions farther away from river mouths are results of local weak bottom stress and associated circulation pattern. Strong seasonal variations exist in the river-derived sediment transport with stronger (weaker) offshore sediment transport occurring in the winter (summer).